2016
DOI: 10.1016/j.ympev.2015.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and structural analyses of cytochrome P450 hydroxylases in sex hormone biosynthesis: Sequential origin and subsequent coevolution

Abstract: Biosynthesis of steroid hormones in vertebrates involves three cytochrome P450 hydroxylases, CYP11A1, CYP17A1 and CYP19A1, which catalyze sequential steps in steroidogenesis. These enzymes are conserved in the vertebrates, but their origin and existence in other chordate subphyla (Tunicata and Cephalochordata) have not been clearly established. In this study, selected protein sequences of CYP11A1, CYP17A1 and CYP19A1 were compiled and analyzed using multiple sequence alignment and phylogenetic analysis. Our an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 73 publications
(111 reference statements)
1
25
0
Order By: Relevance
“…Noteworthy, no CYP19, i.e. the aromatase, was identified which is also consistent with other reported observations in invertebrates [129,130].…”
Section: Reductive Conjugative and Oxidative Biotransformationsupporting
confidence: 92%
“…Noteworthy, no CYP19, i.e. the aromatase, was identified which is also consistent with other reported observations in invertebrates [129,130].…”
Section: Reductive Conjugative and Oxidative Biotransformationsupporting
confidence: 92%
“…The CYP17A1 rs743572 (-34T>C) polymorphism was found to be a strong protective factor against HCC development in both the high-risk HCV/HBV-positive group and healthy individuals. CYP17A1 is an enzyme that plays a critical role in the biosynthesis of steroid hormones by catalyzing both 17a-hydroxylase and 17, 20-lyase activities[ 38 ]. Some data derived from animal models and human epidemiologic studies have demonstrated that estrogens play an essential role in hepatocarcinogenesis; however, the exact mechanism underlying the effect of estrogen levels on HCC development is currently controversial[ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Cyp19a1 gene encodes the enzyme aromatase that is responsible for converting androgens to estrogens [32]. Estrogen plays an important role in ovarian differentiation in fish species, since administration of estrogens can reverse genetic males to phenotypic females [33,34].…”
Section: Discussionmentioning
confidence: 99%